Cities and rural transformation: A spatial analysis of rural youth livelihoods in Ghana - Diao, Xinshen; Fang, Peixun; Magalhaes, Eduardo; Pahl, Stefan; Silver, Jed (International Food Policy Research Institute, 2017)
Urbanization has had a major impact on livelihoods in Ghana and throughout Africa as a whole. However, much research on urbanization has focused on effects occurring within cities, while there is insufficient understanding of its effects on rural areas. This paper examines the impact of urbanization—through a typology of districts—on rural livelihoods in Ghana. The country’s districts are classified into seven spatial groups according to the size of the largest city in each district in southern and northern Ghana. The paper does not address rural–urban migration but instead focuses on the livelihoods of rural households. In contrast to the extensive literature focusing on the effects of urbanization on individuals, we assess its impacts on individual rural households as a whole, with a particular focus on youth-headed households. Many rural households have shifted their primary employment from agriculture to nonagriculture, especially in the more urbanized South. In contrast, change in livelihood diversification within rural households with family members’ primary employment in both agriculture and nonagriculture appears much less rapid. Rural youth-headed households are significantly more associated with the transition away from agriculture than households headed by other adults, and such trends are stronger in locations closer to larger cities, particularly in the South. Although the nonagricultural economy is becoming increasingly important for rural households, contrary to expectations, the probit model analysis in this paper shows that agricultural production does not appear to be more intensified—in terms of modern input use—in the more urbanized South, and youth do not show greater agricultural technology adoption than other adults, indicating that the constraints against modern input adoption may be binding for all farmers, including youth and farmers in more urbanized locations. We also find that rural poverty rates are consistently lower among nonagricultural households, and the share of middle-class population is also disproportionally higher among rural nonagricultural households than agricultural households. While the probit analysis confirms the positive relationship between being a nonagricultural household and being nonpoor or becoming middle class after controlling for all other factors, education seems to play the biggest role. As rural youth become more educated and more households shift from agriculture to the rural nonfarm economy, a different range of technologies for agricultural intensification is necessary for agriculture to be attractive for youth. A territorial approach and related policies that integrate secondary cities and small towns with the rural economy deserve more attention such that the diversification of rural livelihoods can become a viable alternative or complement to rural–urban migration for youth.